DETECTION OF PROSTATE CANCER: A REVIEW - Rani, Pratibha; Singh, Kamaldeep; Arjuna, Anania; Devi, Savita (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Prostate cancer is the most commonly diagnosed non-cutaneous cancer in men. Prostate-specific antigen (PSA) is the biomarker used for the screening of prostate cancer and other prostate-related problems. Not only the genetic factors are involved dietary factors, environmental factors but also responsible for the development of prostate cancer. Risk factors such as family history, age, chemical exposure, infection, and smoking are at the peak point for the development of prostate disease. Advanced age is one of the main risk factors. Radical prostatectomy is the most common therapy for small group of patients with high-grade tumors. Early screening of PSA reduces the incidence rate of prostate cancer. Mostly prostate abnormalities are seen in among male patients above the age of 50 years or older. In worldwide population, the epidemiology of prostate cancer is high in western countries and less in Asian countries.